Pastoralist Robha Abekeri is at COP27 representing the voice of youth in charting pastoralism’s future - Spinelli, Madison (CGIAR System Organization, 2022)
Robha Murha Abekeri attended the inaugural Vision for Pastoralist Youth Conference 2026. Gathering at Lukenya University in Kenya from the 27th to the 29th of September 2022, Robha and 27 other young pastoralists from Kenya, Ethiopia and Tanzania came together to discuss the challenges and opportunities facing youth in pastoralism.